Efektivitas Kelas Literasi Informasi Asynchronous Dalam Masa Pandemi COVID-19 Menurut Mahasiswa Universitas Pelita Harapan - Yanni Karina (Ikatan Pustakawan Indonesia, 2021)
During COVID-19 pandemic situation, a lot of library services, especially higher education libraries, are demanded to be still running despite the physical limitation. Media transfer of the said services require a lot of adaptation, and a lot of instruction needs to be handed to the students whose information seeking pattern are changed to be fully digital and online. Because of that, information literacy classes are needed to train them to face those issues. The increasing demand for information literacy classes has led to innovations in asynchronous information literacy classes where participants get information literacy materials and practices that aim to help write final assignments independently without much help from librarians, so more students can be aided compared to face to face virtual classes. These new methods of information literacy by the library need to be tested and evaluated to get the data of whether it can run properly and effectively. This study aims to measure how effective the asynchronous information literacy class that are run by the library of Universitas Pelita Harapan with the Moodle platform according to the student user base, in terms of materials, class processes and systems, and teaching media. Evaluation questionnaires totaling 33 questions on a Likert scale were distributed to participants near the end of the class. The results showed that the asynchronous information literacy class was adequate, the participants could understand and follow the class well, with several points that needed improvement, such as places for discussion and questions, alternative media, and some technical matters on the Moodle site that hindered learning.